Study of neuroprotective and insulinotropic activities of hydroponic Teucrium polium L in condition ovariectomy. - Chavushyan, V. A.; Simonyan, K. V.; Galstyan, H. M.; Meliksetyan, I. B. (Морфологія / Morphologia / Morfologìâ, 2012)
The increased interest to the neuroprotective medical plants is caused by modulator influence of plant flavonoids on the functioning of synaptic mechanism. The aim of present study was the electrophysiological and morphohistochemical study of neuroprotective effectivity of Teucrium polium in condition of neurodegeneration induced by ovariectomy (OVX). Teucrium polium L was cultivated in open-air hydroponics for the purpose of enrichment of chemical composition by flavonoids and phenilglycosides. The extracellular registration of spiking activity of hippocampal single neurons by high-frequency stimulation of entorhinal cortex after 6 weeks of bilateral ovariectomy (OVX), detected failures of excitatory and inhibitory responses of norm. Also it showed a deficit of neurotransmission and disturbance of synaptic transmission by sharp increase of areactive units. Intramuscular injection of Teucrium polium (20 mg/kg, during 3 weeks), promotes the reorganization of neuronal circuitries of cortex-hippocampus, starting from 3 week after OVX, by modulation of anomalous synaptic activity, according to criteria of intensity of excitatory and inhibitory responses, as well as the balance of areactive and reactive units. Morphological and histochemical study points to neuroprotective effectivity of Teucrium polium in condition of OVX according to the positive changes in the structural properties of neurons and high phosphatase activity in all hippocampal regions, that, in general, defines the cellular survival. Teucrium polium in the conditions of ОVХ shows insulinotropic activity bringing the glucose level in the blood to the initial value.